Post-exercise Endothelium-Dependent Vasodilation Is Dependent on Training Status - Kapilevich, L. V.; Kologrivova, V. V.; Zakharova, A. N.; Mourot, Laurent (Frontiers in Physiology, 2020)
The effect of training status on post-exercise flow mediated dilation (FMD) is not well characterised. We tested the hypothesis that the more trained subjects have a lower reduction in FMD after an acute bout of aerobic exercise. Forty-seven men (mean ± SD, age: 20.1 ± 1.2 years, body mass: 75.5 ± 5.1 kg, height 178.1 ± 5.4 cm) were divided into 5 groups with different training characteristics (sedentary, 2 different groups of active subjects, two different groups of welltrained subjects -runners and weightlifters). Brachial artery FMD was assessed before and immediately after a bout of cycling exercise at a relative intensity determined using a heart rate of 170 bpm (Physical Work Capacity -PWC170). At baseline, a progressive increase in FMD was observed with higher training status, if training remained moderate. Indeed, FMD was reduced in the most highly-trained participants compared to those who were moderately-trained. After PWC170, FMD did not significantly change in sedentary and highly trained runners, significantly increased in the 2 groups of active subjects but significantly decreased in highly trained weightlifters. These results showed that endothelium-dependent vasodilation evaluated using brachial FMD is maintained or improved following acute aerobic exercise in moderately trained participants, but not in well-trained participants, and especially if they participate in resistance training.